Synthesis and evaluation analysis of the indicator information in nuclear safeguards applications by computing with words - Liu, Jun; Ruan, Da; Carchon, Roland (Zielona Góra: Uniwersytet Zielonogórski)
This paper aims at the handling and treatment of nuclear safeguard relevant information by using a linguistic assessment approach. This is based on a hierarchical analysis of a State's nuclear activities in a multi-layer structure of the evaluation model. After a hierarchical analysis of the State's nuclear activities on the basis of the IAEA Physical Model, the addressed objective is divided into several less complex levels.
Keywords: safeguards; computing with words; decision-making; physical model